The Effectiveness of Core Models with Scaffolding to Improve The Mathematical Connection Skill - Yulianto, Alfany Rahman; Rochmad, Rochmad; Dwidayati, Nur Karomah (Journal of Primary Education)
The purpose of this study was to determine the effectiveness of CORE learning models with scaffolding in improving the students' mathematical connection skills. The population of this study was the grade V students of SDN 2 Bobotsari, Purbalingga Regency Academic Year of 2017/2018. Sampling was done by using simple random sampling. Data collection technique was used mathematical connection skill tests, observation, and documentation respectively. This study was analyzed by using t-test. The results show that (1) the mathematical connection skill using the CORE model with Scaffolding have reached 75% of classical completeness, (2) the average mathematical connection skill using the CORE model with Scaffolding was better than the average mathematical connection skill using the CORE model, (3) the increasing in the average mathematical connection skill using the CORE model with Scaffolding is better than the increasing in the average mathematical connection skill using the CORE model only. Based on the results above, it can be concluded that the CORE model with Scaffolding is effective in improving students' mathematical connection skills.